Estética do apocalipse: (re) considerações acerca da (des) arborização urbana de Natal e seu contributo à saúde pública - Medeiros, Eugênio Mariano Fonsêca de (2003)
This study intends to establish a relation between environmental degradation, particularly the devastation of the green canopy, and public health. Utilizing a mapping of the trees included in the researched area, each individual tree was analyzed according to its age, taxonomic listing, architecture, shape and size (determined by aesthetic/convenience reasons or deformed by pruning). Initially investigated were the covert reasons lying underneath the constant aggression against trees (which many times seem to contain elements of hatred and contempt) within the urban environment. In addition to that, the aspects concerning environmental modifications and the consequent impact on public health were also assessed. Two main problems promptly emerged as a result of the removal of trees: a) without a canopy to protect the areas, they became subject to winds directly blown from SW Africa and impregnated with aerosol partic les, which are common causes for respiratory disorders and, b) direct UV solar radiation, which causes some types of skin cancers and eye disorders. To reach such results, we studied the origins and formation of UV radiation induced cancers and searched for the UV radiation spectra of action, e.g., usual intensity and quantity reaching clear and shadowed spaces in a certain area and its consequences. In a second instance, we also searched for pertinent data resources in order to confirm the increase of skin cancer cases due to exposure to UV radiation and the relation between the destruction of the green canopy and the above mentioned problems. We believe that a few significant results have been achieved by this study, namely: the relation between a culture based on medieval beliefs and its consequences on the environment; how this culture exploits and deforms nature in pursuit of financial and psychological interests to a point of transforming the landscape into a copy of something devoid of any relation to latitude and altitude; and above all, the indifference concerning the alarming results carried by these modifications